Strategi Humas dan Protokol Pemerintah Daerah Bengkulu Tengah dalam Menyampaikan Informasi kepada Masyarakat - Dete Konggoro; Femalia Valentine; Destriani Destriani (Jurnal Dakwah dan Komunikasi, 2022)
Writing related to Strategy, Public Relations and Protocol, conveys information to the people of Bengkulu Tengah, as a young district but isolated from technological advances, it reviews the strategies used by public relations and protocols in Bengkulu Tengah in providing satisfaction and comfort for the people of Central Bengkulu. Writing methods and techniques used in compiling the Field Work Practice (PKL) report, the subject of this research is T. Ikchwan. SY. As Head of Sub Division of Public Relations and Protocol of Central Bengkulu Regency. Collecting data in this study using observation, interview, and documentation techniques. Data qualitatively . based on the exposure of the research results are: socialization, using mass media both print and electronic, using WhatsApp Grub. In functionality to convey information to the public.